PS-B09-7: NON-DIPPER BLOOD PRESSURE CAUSED BY INTERMITTENT HYPOXIA AND ITS POSSIBLE MECHANISM IN THE KIDNEY. (January 2023) - Ueda, Kohei; Yeerbolati, Alimila; Lijuan, Liang; Ogura, Sayoko; Takase, Mai; Goda, Nobuhito; Shimosawa, Tatsuo
Abstract : Background: Non-dipper, less than 10% decrease of blood pressure in nighttime than daytime, is one of the strongest risk factor of cardiovascular diseases among hypertensive disorders. High prevalence of non-dipper among patients of sleep-apnea syndrome suggests intermittent hypoxia in nighttime as the mechanism of non-dipper, although it is still to be revealed. Purpose: To identify the mechanism of non-dipper caused by intermittent hypoxia in nighttime. Method: C57Bl/6-background male mice were kept under 8AM-8PM of light and 8PM-8AM dark cycle in closed air-conditioned system which could decrease the O2 level from 21% room air to 5% every 3 minutes. Mice were divided into two groups, normoxia (NX) or intermittent hypoxia (IH), and were kept for two weeks under room air thoroughly or under the IH only during 8 AM to 5 PM respectively. The mice were euthanized at 12PM and kidneys were obtained. Blood pressure (BP) of left carotid artery was recorded by radio-telemetry during the latter one week. To evaluate diurnal change in BP, BPs of 8AM-5PM (inactive) and 5PM-8AM (active) were compared in each of NX and IH mice. Kidney lysate was fractionated by ultracentrifuge to obtain membrane fraction of protein. Result: BP of NX mice in the active phase was significantly higher than the inactive phase, although such diurnal change was not observed in IH mice, demonstrating a development of non-dipper pattern by IH. In the kidney lysates, membrane protein expression levels of phosphorylated-Na + -Cl- cotransporter (NCC) and Na + -K + -Cl- cotransporter 2 (NKCC2) were significantly increased in IH mice compared to NX mice, but those of full-length and cleaved form of ENaCα were not changed. Transcriptional expression levels of Sgk1, Gilz, Per1/2 and Cry1/2 were significantly increased and those of Bmal1 and Clock were decreased in IH mice compared to those of NX mice. Conclusion: These data suggest that defect in molecular clock of the kidney and sodium reabsorption augmented by NCC and/or NKCC2 in the kidney contributes to the development of non-dipper.